Mobile phone use among university students from Isfahan (Iran) and Malaga (Spain). Comparative study in the social and academic field. - Barquín-Ruiz, Francisco Javier; Naghavi, Azam (My University, 2017)
The work presents a comparative analysis of mobile phone use by university students from two universities, a group from Isfahan (Iran) and another from Málaga (Spain). To do this, two groups of young people (90 students from the Faculty of Education of Isfahan and 108 students from the University of Málaga) responded to an online survey translated to Farsi, which analyzed several of the items. The data indicate that the presence and use of the mobile is very widespread among the young population. Nine students out of ten keep the mobile on forever. Although differences are observed in the use of applications, times, etc., and in the case of the sudents of Isfahan it seems to be used more frequently in almost all sections (social networks, informal chat, photographs, etc.) than its Equals of Spain. The results confirm the strong implantation of the mobile phone in the social life of young people but not so much as an academic or professional resource of the same.
Keywords: Estudiantes universitarios - Redes sociales; Social media; Students; Mobile phone; Comparative